Neuroprotective role of hypothermia in hypoxic-ischemic brain injury: Combined therapies using estrogen - Toro Urrego, Nicolas (2018)
Hypoxic-ischemic brain injury is a complex network of factors, which is mainly characterized by a decrease in levels of oxygen concentration and blood flow, which lead to an inefficient supply of nutrients to the brain. Hypoxic-ischemic brain injury can be found in perinatal asphyxia and ischemic-stroke, which represent one of the main causes of mortality and morbidity in children and adults worldwide. Therefore, knowledge of underlying mechanisms triggering these insults may help establish neuroprotective treatments. Selective Estrogen Receptor Modulators and Selective Tissue Estrogenic Activity Regulators exert several neuroprotective effects, including a decrease of reactive oxygen species, maintenance of cell viability, mitochondrial survival, among others. However, these strategies represent a traditional approach of targeting a single factor of pathology without satisfactory results. Hence, combined therapies, such as the administration of therapeutic hypothermia with a complementary neuroprotective agent, constitute a promising alternative. In this sense, the present review summarizes the underlying mechanisms of hypoxic-ischemic brain injury and compiles several neuroprotective strategies, including Selective Estrogen Receptor Modulators and Selective Tissue Estrogenic Activity Regulators, which represent putative agents for combined therapies with therapeutic hypothermia.